The RRM domain–containing protein Rbp3 interacts with ribosomes and the 3’ ends of mRNAs encoding photosynthesis proteins - Luisa Hemm; Elisabeth Lichtenberg; Stefan Tholen; Viktoria Reimann; Kenta Kakazu; Sotaro Machida; Moontaha Mahbub; Oliver Schilling; Annegret Wilde; Satoru Watanabe; Conrad W. Mullineaux; Wolfgang R. Hess (Proceedings of the National Academy of Sciences, 2025)
RNA recognition motif (RRM) domain proteins are crucial RNA-binding proteins across all domains of life. In cyanobacteria, single RRM domain proteins are involved in mRNA targeting to the thylakoid membrane and acclimation to certain stress conditions, but many details of their physiological functions and molecular targets have remained unknown. The model cyanobacterium Synechocystis sp. PCC 6803 has a family of three genes encoding the RRM domain–containing proteins Rbp1, Rbp2, and Rbp3. Here, we verified the RNA-binding activity of Rbp3 in vivo and show that cells of a Δ rbp3 deletion strain had a lower photosystem (PS) I:PSII ratio and decreased pigment content and were significantly smaller than wild-type cells. To identify the set of interacting molecules, coimmunoprecipitation experiments were performed with a strain expressing a C-terminally FLAG-tagged Rbp3. Mass spectrometry of the elution fraction suggested physical proximity between Rbp3, ribosomes, and a very small number of other proteins. The most highly enriched transcript in the coeluting RNA fraction was the psaAB mRNA. This was corroborated by fluorescent in situ hybridization analyses showing decreased psaA mRNA signals in Δ rbp3 , and colocalization with Rbp3 fusions to the green fluorescent protein (GFP) in the wild type. Other mRNAs coenriched with Rbp3 encode thylakoid, plasma membrane, and carboxysome proteins. Binding assays using Bio-layer Interferometry validated the Rbp3- psaAB mRNA interaction, indicating a preference for folded RNA segments near or overlapping the respective stop codons.